2010
DOI: 10.1128/jb.00877-10
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Solvent-Producing Bacterium Clostridium carboxidivorans Strain P7 T

Abstract: Clostridium carboxidivorans strain P7T is a strictly anaerobic acetogenic bacterium that produces acetate, ethanol, butanol, and butyrate. The C. carboxidivorans genome contains all the genes for the carbonyl branch of the Wood-Ljungdahl pathway for CO 2 fixation, and it encodes enzymes for conversion of acetyl coenzyme A into butanol and butyrate. Clostridium carboxidivorans strain P7T (equivalent to ATCC BAA-624T and DSM 15243 T ) is an obligate anaerobe that can grow autotrophically with H 2 and CO 2 or CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 6 publications
0
29
0
Order By: Relevance
“…Products include acetate, ethanol, butanol and butyrate. Draft genome sequences are available for C. carboxidivorans [173,174], which contain the genes of the reductive acetyl-CoA pathway as well as enzymes for the conversion of acetyl-CoA into butanol and butyrate. Bruant et al found the strain contains a plasmid and a butanol pathway similar to that of C. acetobutylicum [101].…”
Section: Butanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Products include acetate, ethanol, butanol and butyrate. Draft genome sequences are available for C. carboxidivorans [173,174], which contain the genes of the reductive acetyl-CoA pathway as well as enzymes for the conversion of acetyl-CoA into butanol and butyrate. Bruant et al found the strain contains a plasmid and a butanol pathway similar to that of C. acetobutylicum [101].…”
Section: Butanolmentioning
confidence: 99%
“…While only a single acetogen had been sequenced before mid-2010, several genome sequences have since been released [91,101,102,144,173,174,228]. However, only very few transcriptomic studies have been published to date [54,176], looking at certain sets of genes rather than gene expression on a global basis.…”
Section: Strain Improvementmentioning
confidence: 99%
“…At later culture stages, the acetic acid concentration itself was actually reduced; this was probably due to the consumption of acetic acid as a substrate for further ethanol production. The genomic analysis [33,34] revealed that C. carboxidivorans P7 contains genes that encode domains of aldehyde: ferredoxin oxidoreductase, indicating that P7 cells can metabolize acetate reduction to acetaldehyde and further to ethanol with reduced ferredoxin. Fig.…”
Section: Syngas Fermentation C Carboxidivorans P7 In Mbr and Bcr In mentioning
confidence: 99%
“…Those enzymes from acetogenic and related anaerobes, such as Moorella thermoacetica and Clostridium pasteurianum, are better than other FDHs as reduction catalysts but also show similar catalytic efficiency toward formate oxidation and are considered highly oxygen labile, requiring anaerobic expression and purification as well as anoxic assay conditions (10,11). Clostridium carboxidivorans strain P7 T (equivalent to ATCC BAA-624 T and DSM 15243 T ) was isolated from the sediment of an agricultural settling lagoon after enrichment with CO as the substrate and is an obligate anaerobe that can grow autotrophically with H 2 and CO 2 or CO (fixing carbon via the Wood-Ljungdahl pathway) (12,13). Therefore, when the gene of a selenocysteine-containing formate dehydrogenase H (FDH H ) from the acetogen Clostridium carboxidivorans strain P7…”
mentioning
confidence: 99%